Effects of particle distribution on mechanical properties of magneto-sensitive elastomers in a homogeneous magnetic field - Ivaneyko, D.; Toshchevikov, V.; Saphiannikova, M.; Heinrich, G. (Condensed Matter Physics, 2012)
We propose a theory which describes the mechanical behaviour of magneto-sensitive elastomers (MSEs) under a uniform external magnetic field. We focus on the MSEs with isotropic spatial distribution of magnetic particles. A mechanical model is used in which magnetic particles are arranged on the sites of three regular lattices: simple cubic, body-centered cubic and hexagonal close-packed lattices. By this we extend our previous approach [Ivaneyko~D. et al., Macromolecular Theory and Simulations, 2011, 20, 411] which used only a simple cubic lattice for describing the spatial distribution of the particles. The magneto-induced deformation and the Young's modulus of MSEs are calculated as functions of the strength of the external magnetic field. We show that the magneto-mechanical behaviour of MSEs is very sensitive to the spatial distribution of the magnetic particles. MSEs can demonstrate either uniaxial expansion or contraction along the magnetic field and the Young's modulus can be an increasing or decreasing function of the strength of the magnetic field depending on the spatial distribution of the magnetic particles.